Portuguese consensus on first line treatment of moderate-to-severe psoriasis with a non-TNF inhibitor therapy – a delphi methodology - Tiago Torres; Sofia Magina; Maria João Paiva Lopes (Journal of Dermatological Treatment)
Introduction Psoriasis (PsO) is a common chronic, inflammatory, immune-mediated disease. In 2023, a 4.4% prevalence of PsO was reported in Portugal. Currently, Tumor Necrosis Factor inhibitors (TNFi) are the recommended first-line (1 L) biologic agents in Portugal given their lower cost. However, TNFi may not be suitable for several patients. In these patients, interleukin inhibitors (ILi) should be considered as they provide more effective outcomes and a better safety profile.Methods Qualitative interviews with PsO experts were conducted to identify PsO biologic treatment needs, resulting in an online survey to explore clinical cases focused on subpopulations of PsO. A delphi study evaluated consensus on clinical criteria to initiate non-TNFi therapy in seven predefined subpopulations of patients.Results This study highlights the benefit of starting non-TNFi therapy in all PsO predefined subpopulations. Patients with infection risk, mild heart failure and associated comorbidities, autoimmune diseases and family history of demyelinating disease consensually benefit from starting non-TNFi therapy in 1 L. Several risks associated with latent tuberculosis, advanced age and oncological disease were also evaluated.Conclusion Given the existence of various risks associated with TNFi usage, this clinical perspective overview of Portuguese experts in PsO treatment emphasizes the need for a tailored therapeutic framework in the management of PsO.